Settlement of Juvenile Offenders Based on Restorative Justice - Syafruddin, Syafruddin (Jurnal IUS Kajian Hukum dan Keadilan, 2022)
The establishment of Law No. 11/2012 was a government strategy for dealing with children as offenders and victims of crime. Despite juvenile criminal justice in place, society often stigmatizes child offenders. This study explores the use of restorative justice for children who have committed crimes. The normative method was used for a descriptive analysis of both statutory and case law. The findings showed that relying only on Law No. 11/2012 is not sufficient because each enforcement officer interprets it differently, necessitating the issuance of supporting regulations such as SE Kapolri No. SE/8/VII/2018, Prosecutor’s Office Regulation No. 15/2020, and PERMA No. 4/2014. To be held liable for one’s actions, as set out in Law no. 11/2012, a person must have both the intention to commit a crime and be aware that it will have a direct result in causing injury or physical harm to another person. Restorative justice is often seen as a more appropriate way to handle criminal acts involving children aged 8 and 13 years. At this age, children are still learning and trying to understand what is good and evil, which can lead them to behave in undesirable ways.